The Impact of Visual Media on Enhancing Students' Comprehension of Islamic Religious Education Lessons - Nurul Fadilah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2023)
Teachers must employ ingenuity in developing multimedia and instructional resources to foster greater student engagement and participation in the learning process. Visual media in Islamic education helps enhance students' comprehension of Islamic concepts. Several challenges must be addressed when using visual media in Islamic education. Several challenges that may arise include restricted access and inadequate facilities, insufficient instructor innovation, poor student comprehension, and inadequate school support. To surmount these challenges, it is imperative to undertake measures such as enhancing accessibility and resources, fostering teacher innovation, deepening student comprehension, and bolstering school support. This research employs quantitative methodology, collecting quantitative data by administering Google Forms to Public High School 4 Tarakan students. Utilizing picture media in Islamic Religious Education subjects has been found to enhance student comprehension, as evidenced by the results of this study. Visual media can enhance comprehension, reinforce retention, and facilitate knowledge acquisition. Image media enhances students' comprehension of Islamic Religious Education topics. Visual stimuli can enhance comprehension, reinforce retention, and cultivate student engagement in the educational endeavour. Teachers are responsible for selecting appropriate instructional methods and media, as failure to do so may result in student ennui throughout the delivery of educational content.